Diabetic footwear: is it an assistive technology capable of reducing peak plantar pressures in elderly patients with neuropathy? - Alexandre Faraco de Oliveira; Ana Carolina Bertoletti De Marchi; Camila Pereira Leguisamo
Abstract Introduction: Diabetes Mellitus is a chronic disease with high prevalence in the population in particular among the elderly. The longer time of diabetes, increased the chances of developing complications such as peripheral neuropathy, which is an important factor in the genesis of plantar lesions by changing the distribution and formation of plantar pressure peaks. Objective: Evaluate the influence of an Assistive Technology, therapeutic footwear for diabetics, in the peaks of plantar pressure of elderly. Methods: This was an experimental study of transversal type, composed by 10 elderly, diabetic, with peripheral neuropathy, using as an instrument to measure a baropodometry platform. Were measured peaks of plantar pressure, static and dynamic in three situations: barefoot, the participants' own standard footwear and with therapeutic footwear for diabetics. Data analysis by normal distribution as a single paired sample, applying the ANOVA test. Results: The use of therapeutic footwear for diabetics promoted a reduction in media of peak plantar pressure in the order of 22% in static analysis, and 31% in dynamic analysis. Conclusion: The therapeutic footwear for diabetics was able to produce significant reductions in peak plantar pressure, being more efficient than a common footwear. This effect may contribute to the prevention of injuries associated with the diabetic foot.